Rekomendasi Rencana Anggaran Biaya dari Audit Keselamatan Jalan Tahap Detail Engineering Design (DED) pada Jalan Nasional Provinsi Jambi - Brama Nalendra; Yossyafra Yossyafra; Bayu Martanto Adji (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
From 2016 – 2018 in Jambi province there were 3,543 traffic accidents, with 1,085 deaths. What causes traffic accidents is caused by three factors, human factors themselves, vehicle factors and road infrastructure factors. To reduce the occurrence of traffic accidents, you can eliminate or reduce the causes of traffic accidents, such as improving the safe condition of road infrastructure. The aim of this research is to calculate recommendations for budget plans from the results of road safety audits at the detailed engineering design (DED) stage, totaling six detailed engineering design (DED) documents on Jambi province national roads. This research uses road safety audit guidelines Pd 03 – 2019 – B. From the results of the analysis, the percentage between the safety cost recommendation results compared to the construction cost design (owner estimate) at DED 1 = 6.17%, DED 2 = 0.93%, DED 3 = 16.13%, DED 4 = 7.33%, DED 5 = 0.75% and DED 6 = 8.83% and the combined percentage obtained is 7.05%. Thus, a detailed engineering design (DED) still requires attention in producing a detailed engineering design (DED) that is oriented towards road safety and the costs of physical implementation of the results of road safety recommendations.